2023
DOI: 10.3390/land12051041
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Planning and Green Environment Services: The Contribution of Trail Paths to Sustainable Development

Abstract: Recently land-use planning and green environment services have been considered as inseparable parts of the design of trail paths for a sustainable development. At present there is need of a holistic overview of land uses and land cover, to be linked with the natural environment and regional development. The key determinants of such an approach embody changes in the wake of drivers and anthropocentric changes as well as changes in global greenhouse gases, causing climate change and affecting global biodiversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Restoring a damaged or abandoned wetland to its original functions involves modifying its physical, chemical, or biological properties and this process is known as wetland restoration [29]. Restoration is the process of re-establishing and reconstructing a degraded wetland, and the wetland's functionalities.…”
Section: What Is Restoration?mentioning
confidence: 99%
See 1 more Smart Citation
“…Restoring a damaged or abandoned wetland to its original functions involves modifying its physical, chemical, or biological properties and this process is known as wetland restoration [29]. Restoration is the process of re-establishing and reconstructing a degraded wetland, and the wetland's functionalities.…”
Section: What Is Restoration?mentioning
confidence: 99%
“…Eliminating a threat or stopping the deterioration of wetland conditions is the definition of wetland protection [30]. Volunteer conservation of naturally occurring wetlands is an important component of volunteer wetland restoration, intervention, and protection, in addition to the restoration of endangered ecosystems, the inherent ecosystem service, and species [29,31].…”
Section: What Is Restoration?mentioning
confidence: 99%
“…Other relevant studies revealed the role of trail paths in supporting sustainable land use planning to support feasible and realistic green environment services. Such approaches could demonstrate the priority and the emerging fields of land use planning to create dynamics of trail paths and human interventions to keep a positive environmental footprint (Kyriakopoulos, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for ecological compensation standards from a supply and demand perspective is becoming widely accepted and used in existing studies [26]. Natural capital provides the material basis and environmental conditions for the survival and development of human beings and is characterized by scarcity, mobility, diversity of values, externality, and commonality [27,28]. Therefore, the natural capital accounting system under the perspective of supply and demand opens up new horizons for determining the ecological compensation standard [29].…”
Section: Introductionmentioning
confidence: 99%